Anxiety and depression in patients with multiple sclerosis - O.V. Somilo; S.O. Makarov; O.I. Kalbus; A.V. Sorokin (Medičnì Perspektivi, 2023)
Multiple sclerosis is a chronic progressive inflammatory autoimmune disease of the central nervous system. This disease mainly affects young females and leads to disability of the patient, which causes a significant socio-economic burden which this disease causes. Clinically, multiple sclerosis is characterized by a wide variety of neurological and neuropsychological manifestations: movement disorders, sensory disturbances and cognitive dysfunction. One of the most typical psycho-emotional disorders that occur in patients with multiple sclerosis are anxiety and depression. The article is devoted to the study of the features of these disorders in patients with multiple sclerosis. The purpose of the study is to evaluate and characterize psycho-emotional disorders in patients with relapsing-remitting multiple sclerosis. The study included 105 patients with relapsing-remitting multiple sclerosis who underwent inpatient treatment in the Department of Neurology No. 1 Municipal Institution “Dnipropetrovsk Regional Clinic Hospital named after I.I. Mechnykov" Dnipropetrovsk Regional Council". Among the patients included in the study, there were 74 women (70.5%) and 31 men (29.5%). The largest proportion of those surveyed falls on the age group from 25 to 40 years – 80 (76.2%). All participants were assessed according to the generally accepted scale for multiple sclerosis patients assessment – Expanded Disability Status Scale (EDSS). All study participants were divided into two groups – group 1 and group 2 – according to the degree of disability according to EDSS. Considering that the degree of disability according to EDSS≤3.5 is defined as mild, and most patients had just this level, they were assigned into group 1, patients with a score of 3.5<EDSS≤6.5 points were assigned to group 2 with a moderate degree of disability. The number of participants in group 1 was 73 patients (69.5%), group 2 – 32 (30.5%). The psychoemotional sphere was assessed using validated psychodiagnostic tests: Beck Depression Inventory and the State-Trait Anxiety Inventory. The average level of depression, determined by Beck Depression Inventory, was 16.0 (13.0; 18.0) points among all examined, in patients of the 1st group – 14.0 (11.0; 16.0) points, while in patients of the 2nd group it was significantly higher (p<0.001) and amounted to 19.0 (19.0; 24.5) points. Assessment of the level of anxiety according to State-Trait Anxiety Inventory showed that in the majority of patients (84.8%) the level of reactive anxiety was moderate (31-44 points) and made up 36.0 (34.0; 39.0) points. Indicators of personal anxiety in most cases (69.5%) were low (up to 30 points) and averaged 27.0 (24.0; 31.0) points. It should be noted that the level of reactive anxiety exceeded the level of personal anxiety in the study groups and in general among all examined (p<0.001 for all comparisons). Anxiety and depression are very common psychoemotional disorders in patients with relapsing-remitting multiple sclerosis. The relationship between the degree of depression, as well as personal and reactive anxiety and the degree of disability according to the EDSS, has been revealed, but the origin of these disorders is still not clear. Given the significant influence of psycho-emotional disorders on the quality of life of patients and the course of the disease, timely diagnosis and treatment should be the priority areas of management of patients with multiple sclerosis.